Analisis Overclaim dalam Iklan Dove Serum Body Wash Ditinjau dari Etika Pariwara Indonesia (EPI) - Lailani Octavia Rahmadhani; Kesya Melika; Ahmad Syarif (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study aims to convey and analyze the Dove serum body wash advertising ethics (EPI) guidelines and in accordance with article 9 of Law No. 8 of 1999 concerning Consumer Protection. The method used is a qualitative description with a case study approach and analysis of the Dove advertisement that aired on February 10, 2025 in digital media. The results of the analysis show that the claim of Dove's first serum body wash can be proven factually and does not violate advertising ethics. However, the claim of instant moisturizing and visualization of rapid skin changes are considered excessive and are feared to be misleading consumers. The delivery of an unclear warning sign (*) can strengthen the indication of a violation of the principle of transparency in advertising. This finding shows the importance of implementing ethical principles in making advertisements and the need for further supervision by advertising regulatory agencies so as not to harm consumers and to maintain public trust in the brand.